MANAJEMEN KEPALA SEKOLAH DALAM PENGUATAN PENDIDIKAN KARAKTER SISWA BERBASIS KURIKULUM 2013 DI MTs DARUNNAJAH 2 CIPINING BOGOR - Rizki Ramadani; Arizqi Ihsan Pratama; Musthafa Zahir (Bajang Institute, 2024)
This thesis discusses the principal's management in strengthening student character education based on the 2013 curriculum at MTs Darunnajah 2 Cipining Bogor. In the research that has been carried out, the author formulated a problem formulation, namely 1) How is the principal's management in strengthening student character education based on the 2013 curriculum. Based on the problem formulation, it covers a wide range of various aspects in strengthening student character education based on the principal's management. The research I conducted aimed to understand the management of school principals in strengthening students' character education based on the 2013 curriculum. The results of the research obtained developed hypotheses using theories put forward by experts, especially those closely related to the role and management of school principals. The research was conducted using qualitative descriptive methods in obtaining research results through interviews, observation and documentation methods. This research is aimed specifically at school principals and educational staff.